Gemcitabine enhances cytotoxic activity of effector T-lymphocytes against chemo-resistant cholangiocarcinoma cells - Nunghathai Sawasdee (2020)
© 2019 Elsevier B.V. Cholangiocarcinoma (CCA) can resist chemotherapy resulting in treatment failure. Gemcitabine, a chemotherapeutic drug, can sensitize cancer cells to become susceptible to cytotoxic T-lymphocytes (CTLs). We, therefore, hypothesized that a combination of gemcitabine and CTLs would be more effective for CCA treatment than individual therapy. To test this hypothesis, we conducted an in vitro study using gemcitabine combined with CTLs to treat gemcitabine-resistant CCA (KKU-213) cells. KKU-213 cells were pretreated with gemcitabine and tested for killing by CTLs activated by dendritic cells that were prepared by three different methods, including: (i) monocyte-derived dendritic cells pulsed with cancer cell lysate (Mo-DC + Lys), (ii) self-differentiated dendritic cells pulsed with cancer-cell lysate (SD-DC + Lys), and (iii) SD-DC presenting tumor-associated antigen PRKAR1A (SD-DC-PR). KKU-213 cells pretreated with gemcitabine were killed by CTLs activated by either SD-DC + Lys or SD-DC-PR more efficiently than those activated by Mo-DC + Lys. Furthermore, KKU-213 cells pretreated with a low dose (2 µM) of gemcitabine significantly enhanced the cytotoxic activity of CTLs activated by either SD-DC + Lys or SD-DC-PR at all evaluated effector (E) to target cell (T) ratios. At an E:T ratio of 5:1, KKU-213 cells pretreated with gemcitabine enhanced the cytotoxic activity of CLTs by approximately 2.5-fold (greater than 50% cell death) compared to untreated condition. The upregulation of HLA class I upon pretreatment of KKU-213 cells with gemcitabine may suggest a mechanism that leads to alteration of the antigen presentation process to promote CTL functions. These findings support the concept of combination therapy for overcoming chemo-resistant CCA.